Determinan Kemiskinan Di Sumatera Utara - Anisa Sihombing; Rukiah Rukiah; Utari Evi Cahyani (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to empirically analyze the factors influencing the poverty rate in North Sumatra Province, focusing on Gross Regional Domestic Product (GRDP), Human Development Index (HDI), government expenditure, and zakat. The persistent poverty issue and the uneven reduction of poverty levels across various regencies and cities serve as the primary motivation for this research. Panel data from eight regencies/cities covering the period 2019-2023 were analyzed using panel data regression methods, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Model selection was conducted using the Chow and Hausman tests, and further validated through Robust Least Squares (RLS) to confirm the stability of the estimation results. The analysis reveals that the Fixed Effect Model is the most appropriate. The variables GRDP, HDI, and zakat have a statistically significant negative effect on poverty, while government expenditure shows a positive but statistically insignificant effect. These findings suggest that enhancing human capital quality, fostering inclusive economic growth, and optimizing zakat management are strategic instruments that need to be strengthened in efforts to alleviate poverty in North Sumatra Province.